Estrogen Maintains Skeletal Muscle in Septic Rats Associated with Altering Hypothalamic Inflammation and Neuropeptides - Zhao, Chenyan; Li, Jun; Cheng, Minhua; Shi, Jialing; Shen, Juanhong; Gao, Tao; Xi, Fengchan; Yu, Wenkui (Hormone and Metabolic Research, 2017)
Muscle wasting is one of the main contributors to the worse outcomes in sepsis. Whether estrogen could alleviate muscle wasting induced by sepsis remains unclear. This study was designed to test the effect of estrogen on muscle wasting and its relationship with central alteration in sepsis. Thirty Sprague-Dawley rats were divided into 3 groups: control group, sepsis group, and estrogen treated sepsis group. Animals were intraperitoneally injected with lipopolysaccharide (10 mg/kg) or saline, followed by subcutaneous injection of 17β-estradiol (1 mg/kg) or saline. Twenty-four hours later, all animals were killed and their hypothalamus and skeletal muscles were harvested for analysis. Muscle wasting markers, hypothalamic neuropeptides, and hypothalamic inflammatory markers were measured. As a result, lipopolysaccharide administration caused a significant increase in muscle wasting, hypothalamic inflammation, and anorexigenic neuropeptides (POMC and CART) gene expression, and a significant decrease in orexigenic neuropeptides (AgRP and NPY) gene expression. Administration of estrogen signifcantl attenuated lipopolysaccharide-induced muscle wasting (body weight and extensor digitorum longus loss [52 and 62 %], tyrosine and 3-methylhistidine release [17 and 22 %], muscle ring fnger 1 [MuRF-1; 65 %], and muscle atrophy F-box [MAFbx] gene expression), hypothalamic inflammation (Tumor necrosis factor-α and interlukin-1β [69 and 70%]) as well as alteration of POMC, CART and AgRP (61, 37, and 1008 %) expression.In conclusion, estrogen could alleviate sepsis-induced muscle wasting and it was associated with reducing hypothalamic inflammation and alteration of hypothalamic neuropeptides.
Keywords: estrogen; muscle wasting; sepsis; hypothalamic neuropeptides; central inflammation